FEASIBILITY ANALYSIS ON INDUSTRIAL SYMBIOSIS BETWEEN CEMENT INDUSTRY AND TEA INDUSTRY - Yadav, Shailendra Kumar; Kalaiyarasi, R (International Journal of Environment, 2015)
The project aims at analyzing the feasibility of utilizing cement kiln dust (CKD) in treating wastewater from tea industry with the concept of industrial symbiosis. CKD is the dust collected at the air pollution control device(s) associated with a kiln system from cement industry. A very less percent of CKD is recycled and the rest is land filled /stockpiled; disrupts groundwater through leaching of minerals. Cement Kiln Dust (CKD), rich in CaO, SiO2, behaves as a neutralizing as well as stabilizing agent for tea effluent treatment. The ability of CKD to reduce the BOD, COD, TSS, and phosphates in tea effluent was analyzed and the optimum dosage is determined. The effect of different dosages of Cement Kiln Dust ranging from (1-3) gm/l has been discussed on the bench scale tests. The results show that, for different CKD concentrations, high removal efficiencies of 94.4 and 99.0, 58.9 for BOD, TSS, phosphates and a lower efficiency for COD with 9.09 are achieved for 2.5gm/l. The persistent presence of color providing proteins theaflavins (TF) and the arubigins (TR) from the leftover tea leaves in the effluent imparts the low removal efficiencies of COD. However, the COD value is within the dischargeable limits (CPCB standards). Moreover, a considerable removal efficiency and high SVI of 0.181 makes CKD a feasible coagulant in treating tea effluent with optimum dosage of 2.5g/l. The objective of developing industrial symbiosis network was thus achieved using the CKD to treat wastewater from tea industries. International Journal of Environment Volume-4, Issue-3, June-August 2015 Page: 20-34